Cooperative Learning with Local Wisdom Integrated Through Online Media and the Impact on Student Critical Thinking Skills - Kumala Ratna Dewi; Lalu Hasan Nasirudin Zohri; Zulhalifah Zulhalifah (Pancaran Pendidikan, 2021)
Critical thinking Skills expressed as essential skills in 21st century society, That made critical thibking should be integrated in the learning process. Critical thinking can be implemented through a cooperative learning model integrated with local wisdom. The inclusion of local wisdom in learning procces was a manifestation of the national education mandate. The outbreak of Covid-19 requires learning procces  carried out online. The purpose of this study was to determined the impact of  cooperative learning integrated local wisdom through online media on the student critical thinking skills. The research method based on nonequivalent pretest-posttest control group design, sample determination using census techniques, data collection using multiple choice tests, and data were analyzed using the MANOVA test using SPSS 16.0. The test results produce an average pre-test of Critical Thinking skill in the experimental group of 37.5 while the value of the control group is 53.57 then the average results of the Post-Test of Critical Thinking ability in the experimental group are 67.14, while the control group 57.5. The results of the Test Between Subject Effect analysis yielded a significant value of critical thinking skills of 0.004. Based on these results it can be stated that there is an cooperative learning integrated wisdom through online media has an positive impact on student critical thinking skills in class X at SMAN 8 Mataram.